Woodhouse Heresies - Gaskins, Richard (Victoria University of Wellington Law Review, 2024)
The radical principles behind the 1967 Woodhouse Report were eclipsed by shifting political styles—and gradually abandoned as heretical. We can now turn to Sir Owen's own notion, that "the apparent heresies of one generation become the orthodoxies of the next", to explore how core Woodhouse heresies might themselves perform this transition: providing fresh support for a generation grappling with headline challenges of climate change and pandemic control.